Pengembangan Model Perangkat Pembelajaran IPA Melalui Model Pembelajaran Sekolah Hijau (For The Greening Schools) di Sekolah Dasar - Muhammad Zaini (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2010)
Abstract: Purpose of this research was to develop science teaching tools with using green school model for improvingstudents’ learning process and achievement. The subjects of the research were elementary schools’ teachers and students at Kecamatan Beruntung Baru Kabupaten Banjar. The collected data was analysed by descriptive. Results were: (1) teaching tools based on using green school model with ecosystem topic, (2) try out results of teaching tools in a low category, teaching process in a medium.